Exploring the E-Learning Adoption Intentions of College Students Amidst the COVID-19 Epidemic Outbreak in China - Isaac Kofi Mensah; Guohua Zeng; Chuanyong Luo; Mengqiu Lu; Zhi-Wu Xiao (SAGE Open, 2022)
This research paper investigated the adoption behavior of college students toward the e-learning system amidst the current COVID-19. The model was developed and validated based on the Technology Acceptance Model (TAM) and the partial least squares-structural equation modeling (PLS-SEM) was used to analyze the data. The data was generated from 316 Chinese college students based on the convenient sampling technique. The research outcomes indicate that the perceived ease of use is a significant predictor of the intention to use and perceived usefulness of an e-learning system. To our surprise, perceived usefulness does not determine the intention to use an e-learning system. Computer self-efficacy and technical support respectively were significant determinants of the perceived usefulness and the perceived ease of use of an e-learning system. Interestingly, the study showed that internet experience does not influence students’ sensitivity to the usefulness and ease of use associated with an e-learning system. The theoretical and managerial implications of these results findings are thoroughly interrogated.